Alloy for RTB permanent magnets and method for producing RTB permanent magnets

JP7645121B2Active Publication Date: 2025-03-13TDK CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021058805
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-30
Publication Date
2025-03-13
Estimated Expiration
2041-03-30

Smart Images

  • Figure 0007645121000003
    Figure 0007645121000003
  • Figure 0007645121000004
    Figure 0007645121000004
  • Figure 0007645121000005
    Figure 0007645121000005
Patent Text Reader

Abstract

To provide an alloy for an R-T-B based permanent magnet, which enables the production of an R-T-B based permanent magnet enhanced in magnetic property.SOLUTION: An alloy for an R-T-B based permanent magnet comprises R, T and B, where R is a rare earth element, T is a transition metal element and B is boron. In a cross section thereof, the areal percentage of a fine linear R-rich phase-containing structure is 0.5% or more and 20% or less.SELECTED DRAWING: Figure 7
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an alloy for an RTB permanent magnet and a method for producing an RTB permanent magnet. [Background technology]

[0002] Patent Document 1 describes an invention related to alloy flakes for rare earth magnets, characterized in that the thickness and surface roughness are within specific ranges. By controlling the surface roughness of the casting roll surface to fall within a specific range, the fine R-rich phase region in the alloy flakes for rare earth magnets is reduced, improving the magnetic properties.

[0003] Patent Document 2 describes an invention relating to a method for producing rare earth-containing alloy flakes, characterized in that the shape of the casting surface of a rotating cast roll is a specific shape and the surface roughness of the casting surface of the rotating cast roll is within a specific range. The RTB alloy flakes produced by this production method have a reduced fine R-rich phase region and are excellent in homogeneity.

[0004] Patent Document 3 describes an invention relating to a raw material alloy for RTB magnets, characterized in that the volume ratio of the region where secondary dendrite arms are formed is within a specific range. The formation of secondary dendrite arms refines the structure, and therefore the coercive force of an RTB sintered magnet obtained using this raw material alloy for RTB magnets is improved. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2003-188006 A [Patent Document 2] JP 2004-181531 A [Patent Document 3] International Publication No. 2014 / 156181 Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide an alloy for an RTB permanent magnet that can be used to produce an RTB permanent magnet with improved magnetic properties. [Means for solving the problem]

[0007] In order to achieve the above object, the present invention provides an RTB permanent magnet alloy comprising: The alloy for an RTB-based permanent magnet contains R, T and B, where R is a rare earth element, T is a transition metal element and B is boron, and the area ratio of a fine linear R-rich phase-containing structure in a cross section is 0.5% or more and 20% or less.

[0008] The total area ratio of the fine linear R-rich phase-containing structure and the fine dotted R-rich phase-containing structure in the cross section may be 1.0% or more and 24.0% or less.

[0009] The total area ratio of the chill crystal structure, the fine linear R-rich phase-containing structure, and the fine dotted R-rich phase-containing structure in the cross section may be 1.0% or more and 27.0% or less.

[0010] The content of R may be 29.0 mass % or more and 33.5 mass % or less, and the content of B may be 0.70 mass % or more and less than 0.96 mass %.

[0011] The method for producing an RTB permanent magnet according to the present invention includes a step of pulverizing the above-mentioned alloy for an RTB permanent magnet. [Brief description of the drawings]

[0012] [Figure 1] This is a backscattered electron image of normal tissue. [Diagram 2] This is a backscattered electron image of chill crystal structure. [Diagram 3] This is a backscattered electron image of a structure containing fine dots of R-rich phase. [Figure 4] This is a backscattered electron image of a structure containing fine dots of R-rich phase. [Diagram 5]It is a backscattered electron image of a tissue containing a dot-like R-rich phase. [Figure 6] It is a backscattered electron image of a tissue containing a fine linear R-rich phase. [Figure 7] It is a backscattered electron image of a tissue containing a fine linear R-rich phase. [Figure 8] It is a backscattered electron image of a tissue containing a large dot-like R-rich phase. [Figure 9] It is a schematic diagram of a casting device.

Mode for Carrying Out the Invention

[0013] Hereinafter, the present invention will be described based on the embodiments shown in the drawings.

[0014] <Microstructure of an R-T-B System Permanent Magnet Alloy> The R-T-B system permanent magnet alloy according to this embodiment has R, T, and B, and is an R-T-B system permanent magnet alloy in which R is a rare earth element, T is a transition metal element, and B is boron. And in the cross section, the area ratio of the tissue containing a fine linear R-rich phase described later is 0.5% or more and 20% or less.

[0015] Generally, an R-T-B system permanent magnet alloy has a columnar crystal having an R2T 14 main phase having a B-type crystal structure and an R-rich phase having a higher R content than the main phase.

[0016] In the cross section of the R-T-B system permanent magnet alloy, as shown in the backscattered electron image of FIG. 1, a clear difference can be confirmed between the main phase 11 and the R-rich phase 13, and most of the shapes of the R-rich phases 13 are linear. The tissue 7 (hereinafter referred to as the normal tissue 7) occupies the majority. Most of the main phases 11 contained in the normal tissue 7 are columnar crystals. In the normal tissue 7, the average interval between the R-rich phases (hereinafter referred to as linear R-rich phases) having a linear shape is 2 μm or more. Further, the normal tissue 7 is a tissue in which primary dendrites extend in the direction of solidification of the alloy, in other words, in the thickness direction of the alloy.

[0017] In addition to the normal structure 7, RTB permanent magnet alloys also include structures that include a main phase that is not columnar. A main phase that is not columnar is called a non-columnar crystal, and a structure that includes non-columnar crystals is called a non-columnar crystal structure. A non-columnar crystal structure is a structure in which the primary dendrites do not necessarily extend in the direction of solidification of the alloy.

[0018] The non-columnar crystal structures contained in RTB permanent magnet alloys are mainly classified into six types when distinguishing between structure 1a and structure 1b described below. The six types of non-columnar crystal structures are explained below with reference to drawings (backscattered electron images).

[0019] Figure 2 includes chilled crystal structure 1, which includes structures 1a and 1b. Structure 1a is more different from normal structure 7 than structure 1b. In structure 1a, no clear difference is seen between the main phase and the R-rich phase. The brightness of structure 1a in a backscattered electron image is intermediate between that of the main phase and the R-rich phase. Furthermore, the variation in shading in a backscattered electron image of structure 1a is smooth.

[0020] Structure 1b is closer to normal structure 7 than structure 1a. However, structure 1b shows no clear difference between the main phase and the R-rich phase. The brightness of structure 1b in the backscattered electron image is intermediate between that of the main phase and the R-rich phase. Furthermore, the variation in shading in the backscattered electron image of structure 1b is smooth. Also, unlike structure 1a, structure 1b partially contains linear R-rich phases.

[0021] In the following description, when simply referring to chill crystal structures, no distinction is made between structure 1a and structure 1b.

[0022] 3 and 4 include a fine dot-like R-rich phase-containing structure 3 (hereinafter, sometimes referred to as structure 3). Different alloy pieces are observed in Figs. 3 and 4. In structure 3, a clear difference is observed between the main phase and the R-rich phase. However, compared to the normal structure 7 shown in Fig. 1, in structure 3, the R-rich phase aggregates in dots and is excessively dense. Furthermore, compared to the dot-like R-rich phase-containing structure 4 described below, the dot-like R-rich phase is finer.

[0023] The dot-like R-rich phase contained in the structure 3 has a circle equivalent diameter of 0.3 to 1.5 μm, and the number of dot-like R-rich phases having a circle equivalent diameter of 0.3 to 1.5 μm per unit area is 0.25 pieces / μm 2 That's all.

[0024] Furthermore, structure 3 can be cut into sections where the circle equivalent diameter and density of the dot-like R-rich phase locally differ subtly. The actual cut state is shown by the dotted lines in Figure 4. The cut polygonal regions have a long axis of 10 μm to 120 μm and a short axis of 5 μm to 80 μm. The long axis refers to the longest distance between two parallel lines that contact the polygon on both sides, and the short axis refers to the shortest distance between two parallel lines that contact the polygon on both sides.

[0025] From the above, the number of dot-like R-rich phases with a circle equivalent diameter of 0.3 to 1.5 μm per unit area was 0.25 pieces / μm 2 When the tissue is cut into a polygon, the tissue that exists within the range of the polygon whose major axis and minor axis are within the above range is defined as tissue 3.

[0026] FIG. 5 includes a dot-like R-rich phase-containing structure 4 (hereinafter, sometimes referred to as structure 4). Structure 4 has a larger dot-like R-rich phase itself than structure 3. Furthermore, in the portion where the dot-like R-rich phase aggregates, a phase darker than the main phase exists.

[0027] 6 and 7 include a microstructure 5 containing fine linear R-rich phases (hereinafter, sometimes referred to as structure 5). Different alloy pieces are observed in Figs. 6 and 7. In structure 5, a clear difference is observed between the main phase and the R-rich phase. However, in structure 5, the linear R-rich phases are thinner and excessively denser than in the normal structure 7 shown in Fig. 1.

[0028] The linear R-rich phases contained in the structure 5 have a length of 4 to 125 μm and a width of 0.3 to 10 μm, and the spacing between the linear R-rich phases is 1.0 to 1.8 μm.

[0029] Furthermore, the structure 5 can be cut into sections where the length, width, and density of the linear R-rich phase are subtly different locally. The actual cut state is shown by dotted lines in Figure 7. The cut polygonal regions have a long axis of 30 μm to 200 μm and a short axis of 5 μm to 150 μm.

[0030] From the above, a structure having linear R-rich phases with a length of 4 to 125 μm and a width of 0.3 to 10 μm, the spacing between the linear R-rich phases being 1.0 to 1.8 μm, and when cut into polygons, the major axis and minor axis of the linear R-rich phases being within the above-mentioned ranges, is defined as structure 5.

[0031] FIG. 8 includes a large dot-like R-rich phase-containing structure 6 (hereinafter, sometimes referred to as structure 6). In structure 6, the R-rich phase is aggregated to a large extent. The brightness of the main phase around the aggregated R-rich phase is slightly higher. Also, linear R-rich phases may be sandwiched between the large aggregated R-rich phases.

[0032] The above-mentioned seven normal structures and six types of non-columnar structures can be visually distinguished from the backscattered electron images of the cross sections of the RTB permanent magnet alloy. There is no particular limit to the magnification of the backscattered electron images used to distinguish each structure. For example, it may be 200 to 500 times.

[0033] The present inventors have found that an RTB permanent magnet produced using an alloy for an RTB permanent magnet in which the area ratio of structure 5 is 0.5% or more and 20.0% or less has good magnetic properties. The area ratio of structure 5 may be 1.0% or more, or 3.4% or more. It may also be 19.2% or less.

[0034] The total area ratio of structure 3 and structure 5 may be 1.0% or more and 24.0% or less, 1.1% or more, or 3.6% or more, 23.4% or less, or 3.6% or more and 23.4% or less.

[0035] The total area ratio of the tissue 1a, the tissue 1b, the tissue 3, and the tissue 5 may be 1.0% or more and 27.0% or less. It may be 1.3% or more, may be 4.0% or more, may be 4.3% or more. Also, it may be 26.2% or less.

[0036] The total area ratio of the tissue 1a, the tissue 1b, the tissue 3, the tissue 4, the tissue 5, and the tissue 6 may be 1.2% or more and 36.0% or less, and may be 1.4% or more and 30.3% or less.

[0037] <Composition of the R-T-B based permanent magnet alloy> There is no particular limitation on the composition of the R-T-B based permanent magnet alloy. R represents at least one of rare earth elements. The rare earth elements refer to Sc, Y, and lanthanoid elements belonging to Group 3 of the long-period type periodic table. The lanthanoid elements include, for example, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, etc. The rare earth elements are classified into light rare earth elements and heavy rare earth elements. The heavy rare earth elements refer to Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and the light rare earth elements are rare earth elements other than the heavy rare earth elements. In the present embodiment, from the viewpoint of suitably controlling the manufacturing cost and magnetic properties, it may contain Nd and / or Pr as R. Also, from the viewpoint of particularly improving HcJ, it may contain both light rare earth elements and heavy rare earth elements. There is no particular limitation on the content of the heavy rare earth elements, and it may not contain heavy rare earth elements. The content of the heavy rare earth elements is, for example, 5 mass% or less (including 0 mass%).

[0038] The content of R may be 29.0 mass% or more and 33.5 mass% or less. When the content of R is small, the HcJ of the obtained R-T-B based permanent magnet tends to decrease. When the content of R is large, Br tends to decrease.

[0039] The content of B may be 0.70% by mass or more, or 0.80% by mass or more. The upper limit of the content of B may be less than 1.0% by mass, less than 0.96% by mass, or 0.90% by mass or less. When the content of B is smaller than the stoichiometric ratio, specifically, when it is less than 1.0% by mass, the area ratio of each of the above structures is easily set within the above range. When the content of B is small, HcJ is easily decreased. Furthermore, abnormal grain growth is easily caused when sintering at high temperatures. Furthermore, when sintering at low temperatures, Hk / HcJ is difficult to increase. When the content of B is large, abnormal grain growth is easily caused. And Br is easily decreased.

[0040] T is a transition metal element. It may be Fe alone or Fe and Co. The Co content may be 0% by mass or more and 2.0% by mass or less. If the Co content is small, abnormal grain growth is likely to occur when sintering at high temperatures. Also, it is difficult to increase Hk / HcJ when sintering at low temperatures. If the Co content is large, Br and HcJ decrease. Also, the RTB permanent magnet according to this embodiment tends to be expensive.

[0041] The RTB permanent magnet alloy may contain M. M is one or more selected from Cu, Ga, Zr, and Al. There is no particular limit to the total content of M. It may be 0.1% by mass or more and 2.0% by mass or less.

[0042] There is no particular limit to the Cu content. For example, it may be 0.05% by mass or more and 0.50% by mass or less. By including 0.05% by mass or more of Cu, abnormal grain growth is less likely to occur when sintering at high temperatures. In addition, even when sintering at low temperatures, Hk / HcJ tends to be sufficiently high. By including 0.50% by mass or less of Cu, Br tends to be improved.

[0043] There is no particular limit to the Ga content. For example, it may be 0% by mass or more and 1.0% by mass or less. By including Ga, abnormal grain growth is less likely to occur when sintering at high temperatures. Furthermore, even when sintering at low temperatures, Hk / HcJ tends to be sufficiently high. Furthermore, HcJ tends to be improved. By including 1.0% by mass or less of Ga, Br tends to be improved.

[0044] There is no particular limit to the Al content. For example, it may be 0.05% by mass or more and 1.00% by mass or less. By including 0.05% by mass or more of Al, HcJ is likely to be improved. Furthermore, even when sintering at high temperatures, abnormal grain growth is unlikely to occur. Furthermore, even when sintering at low temperatures, Hk / HcJ tends to be sufficiently high. By including 1.00% by mass or less of Al, Br is likely to be improved.

[0045] There is no particular limit to the Zr content. For example, it may be 0.05% by mass or more and 1.00% by mass or less. By including 0.05% by mass or more of Zr, Hk / HcJ tends to be sufficiently high even when sintered at a low temperature. In addition, abnormal grain growth is less likely to occur even when sintered at a high temperature. By including 1.00% by mass or less of Zr, Br tends to be improved.

[0046] The Fe content is the substantial balance in the components of the RTB permanent magnet alloy. The Fe content being the substantial balance refers to the case where the total content of elements other than R, Fe, Co, B, and M is 1.0 mass% or less.

[0047] The RTB system permanent magnets produced using the alloy for RTB system permanent magnets according to this embodiment are processed into any shape for use. The shape of the RTB system permanent magnet is not particularly limited, and can be any shape, such as a rectangular parallelepiped, hexahedron, flat plate, columnar such as a square column, or a cylindrical shape with a C-shaped cross section.

[0048] Furthermore, RTB permanent magnets include both magnet products made by processing and magnetizing the magnet, and magnet products made by not magnetizing the magnet.

[0049] <Method for manufacturing an alloy for an R-T-B-based permanent magnet> As an example of a method for manufacturing an alloy for an R-T-B-based permanent magnet, a method of manufacturing by a strip casting method using the casting apparatus shown in FIG. 9 will be described.

[0050] The casting apparatus shown in FIG. 9 has a cooling roll 21 and a tundish 23. Although not shown in FIG. 9, the casting apparatus may have components well known as components of a casting apparatus, such as a refractory crucible and a collection container. There is no particular limitation on the type of refractory crucible. Examples include an alumina crucible, a mullite crucible, and a zirconia crucible. There is no particular limitation on the material of the cooling roll 21. Examples include copper, a copper alloy, a material obtained by plating or spraying on the surface of copper, and a material obtained by plating or spraying on the surface of a copper alloy.

[0051] First, raw materials are weighed and mixed so as to have the alloy composition of the target alloy for an R-T-B-based permanent magnet to obtain a raw material mixture.

[0052] Next, the obtained raw material mixture is loaded into a refractory crucible, and the loaded raw material mixture is melted to obtain an alloy melt. There is no particular limitation on the method of melting the raw material mixture. For example, a method of heating a refractory crucible loaded with a raw material mixture by installing it in a high-frequency vacuum induction furnace can be mentioned.

[0053] Then, the obtained alloy melt is cast by a strip casting method using the casting apparatus shown in FIG. 9 to obtain a cast alloy ribbon (alloy for an R-T-B-based permanent magnet). Specifically, the alloy melt 25 is supplied to the internally water-cooled cooling roll 21 via the tundish 23. The alloy melt 25 supplied onto the cooling roll 21 is cooled and separated from the cooling roll 21 on the opposite side of the tundish 23 and recovered as a cast alloy ribbon.

[0054] Of the cast alloy ribbon, the surface in contact with the chill roll 21 is the roll surface, and the surface opposite to the roll surface is the free surface. The roll surface is cooled more rapidly by the chill roll 21 than the free surface. Here, non-columnar crystal structures such as structure 5 are more likely to form when the cooling rate is faster than that of normal structures. Among non-columnar crystal structures, chill crystal structures are more likely to form when the cooling rate is particularly fast. Therefore, chill crystal structures and non-columnar crystal structures are more likely to form on the roll surface than on the free surface. Note that the roll surface is on the left side in all of Figures 1 to 8.

[0055] There is no particular restriction on the position of the observation range for calculating the area ratio of each of the above structures, but the length in the direction parallel to the thickness direction is preferably a length that includes the entire RTB permanent magnet alloy, i.e., the thickness of the alloy. This is to ensure that both the vicinity of the roll surface and the vicinity of the free surface are included in the observation range. The length in the direction perpendicular to the thickness direction is preferably set to at least 180 μm. In other words, the observation magnification is determined so that the observation range includes at least a range of 180 μm × (thickness of the alloy).

[0056] The area ratio of each structure varies mainly depending on the temperature of the molten alloy 25 (casting temperature), the composition of the molten alloy 25, the roll surface roughness Rz of the chill roll 21, the shape of the unevenness that affects the roll surface roughness Rz, the molten metal head pressure 27, the roll circumferential speed of the chill roll 21, and the supply speed of the molten alloy 25 to the chill roll 21 (the supply speed per unit contact width between the molten alloy 25 and the chill roll 21). The temperature of the molten alloy 25 is, for example, 1300 to 1600°C. The roll surface roughness Rz of the chill roll 21 is, for example, 10 to 50 μm. The roll circumferential speed of the chill roll 21 is, for example, 0.5 to 2.5 m / s. The supply speed of the molten alloy 25 to the chill roll 21 is, for example, 0.5 to 2.5 kg / (min cm).

[0057] The following describes the molten metal head pressure 27. The molten metal head pressure 27 refers to the depth of the molten alloy 25 in contact with the cooling roll 21. The greater the molten metal head pressure 27, the stronger the pressure with which the molten alloy 25 is pressed against the cooling roll 21 by its own weight. Therefore, the greater the molten metal head pressure 27, the stronger the adhesion between the molten alloy 25 and the cooling roll 21, and the higher the heat transfer rate from the molten alloy 25 to the cooling roll 21. At the same time, the length of the molten alloy 25 in contact with the cooling roll 21 also changes. Therefore, if other conditions are the same, the higher the molten metal head pressure 27, the thicker the cast alloy strip. In practice, the molten metal head pressure 27 is appropriately selected in combination with other casting conditions.

[0058] As described above, the faster the cooling rate, the easier it is to form a non-columnar crystal structure (chill crystal structure). Therefore, the greater the molten metal head pressure 27, the greater the tendency for the area ratio of the non-columnar crystal structure (chill crystal structure) to be larger.

[0059] As a method of increasing the molten metal head pressure 27, a method of increasing the amount of the molten alloy 25 in the tundish 23 can be mentioned. As a method of increasing the amount of the molten alloy 25 in the tundish 23, a method of increasing the supply rate of the molten alloy 25 to the tundish 23 can be mentioned. If the supply rate of the molten alloy 25 to the tundish 23 increases, the cast alloy strip becomes thicker. As a method of increasing the molten metal head pressure 27 without changing the thickness of the cast alloy strip, a method of increasing the peripheral speed of the cooling roll 21 can be mentioned.

[0060] That is, when producing a cast alloy strip of the same thickness, when the supply rate of the molten alloy 25 is high and the peripheral speed of the cooling roll 21 is high, the molten metal head pressure 27 becomes large, and when the supply rate of the molten alloy 25 is low and the peripheral speed of the cooling roll 21 is low, the molten metal head pressure 27 becomes small.

[0061] <Method for manufacturing an R-T-B based permanent magnet> There is no particular limitation on the method for manufacturing an R-T-B based permanent magnet using the alloy for an R-T-B based permanent magnet manufactured by the above method. For example, a method having the following steps can be mentioned. (a) Crushing process for crushing RTB permanent magnet alloys (b) A molding step for molding the obtained alloy powder. (c) Sintering process to obtain RTB permanent magnets by sintering the green body (d) Aging treatment process for aging RTB permanent magnets (e) Cooling process for cooling RTB permanent magnets (f) Processing process for RTB permanent magnets (g) Grain boundary diffusion process in which heavy rare earth elements are diffused into the grain boundaries of RTB permanent magnets (h) Surface treatment process for RTB permanent magnets

[0062] [Crushing process] The RTB permanent magnet alloy is pulverized (pulverization process). The pulverization process includes a coarse pulverization process in which the alloy is pulverized to a particle size of several hundred μm to several mm, and a fine pulverization process in which the alloy is pulverized to a particle size of about several μm.

[0063] (Coarse grinding process) The RTB permanent magnet alloy is coarsely pulverized until the particle size is about several hundred μm to several mm (coarse pulverization step). This produces a coarsely pulverized powder of the RTB permanent magnet alloy. The coarse pulverization can be performed, for example, by absorbing hydrogen into the RTB permanent magnet alloy, then releasing hydrogen based on the difference in the amount of hydrogen absorbed between different phases, and dehydrogenating the alloy to cause self-destructive pulverization (hydrogen absorption pulverization).

[0064] The coarse pulverization step may be performed in an inert gas atmosphere using a coarse pulverizer such as a stamp mill, a jaw crusher, or a Braun mill, other than the hydrogen absorption pulverization method described above.

[0065] The oxygen concentration is adjusted by controlling the atmosphere in each manufacturing process. From the viewpoint of obtaining high magnetic properties, the oxygen content of the finally obtained RTB permanent magnet may be reduced. To achieve this, the oxygen concentration in each process from the grinding process to the sintering process described below may be set to 100 ppm or less.

[0066] (Fine grinding process) After the RTB permanent magnet alloy is coarsely pulverized, the obtained coarsely pulverized powder of the RTB permanent magnet alloy is finely pulverized until the average particle size is about several μm (fine pulverization step). This produces finely pulverized powder of the RTB permanent magnet alloy. By further finely pulverizing the coarsely pulverized powder, finely pulverized powder having particles of, for example, 1 μm to 10 μm, or 3 μm to 5 μm can be obtained.

[0067] Fine pulverization is performed by further pulverizing the coarsely pulverized powder using a fine pulverizer such as a jet mill, ball mill, vibration mill, wet attritor, etc., while appropriately adjusting conditions such as pulverization time. A jet mill is a method in which a high-pressure inert gas (e.g., N2 gas) is released from a narrow nozzle to generate a high-speed gas flow, and this high-speed gas flow accelerates the coarsely pulverized powder of the raw alloy, causing collisions between the coarsely pulverized powder of the raw alloy and with a target or the wall of a container, thereby pulverizing the powder.

[0068] When the coarsely pulverized powder of the raw alloy is pulverized, a pulverization aid such as zinc stearate, urea, stearic acid amide, or oleic acid amide can be added to obtain a finely pulverized powder with a high degree of orientation during compaction.

[0069] [Molding process] The pulverized powder is molded into the desired shape (molding process). In the molding process, the pulverized powder is filled into a die surrounded by an electromagnet and pressurized to mold the pulverized powder into any shape. This is done while a magnetic field is applied, which creates a specific orientation in the pulverized powder, and molding is performed in the magnetic field with the crystal axes aligned. This produces a molded body. The resulting molded body is oriented in a specific direction, resulting in an RTB permanent magnet with stronger magnetic anisotropy.

[0070] The pressure during molding may be 30 MPa to 300 MPa. The magnetic field applied may be 950 kA / m to 1600 kA / m. The magnetic field applied is not limited to a static magnetic field, and may be a pulsed magnetic field. A static magnetic field and a pulsed magnetic field may also be used in combination.

[0071] As a molding method, in addition to the dry molding in which the finely pulverized powder is molded as is as described above, wet molding in which a slurry in which the finely pulverized powder is dispersed in a solvent such as oil can also be applied.

[0072] The shape of the green body obtained by compacting the finely pulverized powder is not particularly limited, and can be any shape depending on the desired shape of the RTB permanent magnet, such as a rectangular parallelepiped, flat plate, column, ring, etc.

[0073] [Sintering process] The green body obtained by molding in a magnetic field and forming into the desired shape is sintered in a vacuum or inert gas atmosphere to obtain an RTB permanent magnet (sintering process). The sintering temperature needs to be adjusted depending on various conditions such as the composition, the pulverization method, the particle size and particle size distribution, etc. The green body is sintered, for example, by heating in a vacuum or in the presence of an inert gas at 1000°C to 1200°C for 1 hour to 48 hours. This causes liquid phase sintering of the finely pulverized powder, and an RTB permanent magnet (sintered body of RTB magnet) with an increased volume ratio of main phase particles is obtained. After sintering the green body to obtain the sintered body, the sintered body may be rapidly cooled from the viewpoint of improving production efficiency.

[0074] [Aging treatment process] After sintering the compact, the RTB permanent magnet is subjected to an ageing treatment (aging treatment step). After sintering, the RTB permanent magnet is subjected to an ageing treatment by, for example, holding the obtained RTB permanent magnet at a temperature lower than that at the time of sintering. The aging treatment may be, for example, a two-stage heating at a temperature of 700°C or higher and 1000°C or lower for 10 minutes to 6 hours, and then a one-stage heating at a temperature of 500°C to 700°C for 10 minutes to 6 hours, or a one-stage heating at a temperature of about 600°C for 10 minutes to 6 hours, and the treatment conditions are appropriately adjusted depending on the number of times the aging treatment is performed. Such an aging treatment can improve the magnetic properties of the RTB permanent magnet. The aging treatment step may also be performed after the processing step described below.

[0075] [Cooling process] After the RTB permanent magnet is subjected to aging treatment, the RTB permanent magnet is rapidly cooled in an Ar gas atmosphere (cooling step). This makes it possible to obtain the RTB permanent magnet according to the present embodiment. The cooling rate is not particularly limited, and may be 30°C / min or more.

[0076] [Processing process] The obtained RTB permanent magnet may be processed into a desired shape as necessary (processing step). Examples of processing methods include shaping such as cutting and grinding, and chamfering such as barrel polishing.

[0077] [Grain boundary diffusion process] A heavy rare earth element may be further diffused into the grain boundaries of the processed RTB permanent magnet (grain boundary diffusion step). There are no particular limitations on the method of grain boundary diffusion. For example, it may be carried out by attaching a compound containing a heavy rare earth element to the surface of the RTB permanent magnet by coating or vapor deposition, etc., and then carrying out a heat treatment. It may also be carried out by carrying out a heat treatment on the RTB permanent magnet in an atmosphere containing vapor of the heavy rare earth element. Grain boundary diffusion can further improve the HcJ of the RTB permanent magnet.

[0078] [Surface treatment process] The RTB permanent magnet obtained by the above steps may be subjected to surface treatment such as plating, resin coating, oxidation treatment, chemical conversion treatment, etc. (surface treatment step).

[0079] In this embodiment, the processing step, the grain boundary diffusion step, and the surface treatment step are performed, but these steps do not necessarily have to be performed.

[0080] The RTB permanent magnet according to this embodiment obtained as described above has good magnetic properties and a wide sintering temperature range, which makes it possible to stably produce the RTB permanent magnet according to this embodiment.

[0081] The RTB permanent magnet according to this embodiment obtained in this manner is suitable for use as a magnet in, for example, a surface permanent magnet (SPM) rotating machine with a magnet attached to the rotor surface, an interior permanent magnet (IPM) rotating machine such as an inner rotor brushless motor, a permanent magnet reluctance motor (PRM), etc. Specifically, the RTB permanent magnet according to this embodiment is suitable for use in spindle motors and voice coil motors for rotating hard disks in hard disk drives, motors for electric and hybrid cars, motors for electric power steering in automobiles, servo motors for machine tools, motors for vibrators in mobile phones, motors for printers, motors for generators, etc.

[0082] The present invention is not limited to the above-described embodiment, and various modifications can be made within the scope of the present invention. EXAMPLES

[0083] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0084] (Preparation of alloys for RTB permanent magnets) Nd metal (purity 99% by mass or more), Nd-Pr alloy (didymium, purity 99% by mass or more), Tb metal (purity 99% by mass or more), ferroboron (Fe content 80% by mass, B content 20% by mass), Fe metal (purity 99% by mass or more), Co metal (purity 99% by mass or more), Zr metal (purity 99% by mass or more), Cu metal (purity 99% by mass or more), Al metal (purity 99% by mass or more), and Ga metal (purity 99% by mass or more) were weighed out to obtain the alloy composition shown in Table 1 below and mixed to obtain a raw material mixture. In Table 1, "T.RE" is the total content (mass%) of rare earth elements (Nd, Pr, Dy, and Tb), "T.RL" is the total content (mass%) of light rare earth elements (Nd and Pr). "bal." is the remainder. The Fe content is indicated as "bal." to indicate that the Fe content is the remainder when the entire RTB permanent magnet alloy, which contains elements other than the elements listed in Table 1, is taken as 100 mass%.

[0085] The obtained raw material mixture was loaded into an alumina crucible. The alumina crucible loaded with the raw material mixture was placed in a high-frequency vacuum induction furnace, and the atmosphere inside the high-frequency vacuum induction furnace was then replaced with Ar. The high-frequency vacuum induction furnace was then heated to melt the raw material mixture loaded into the alumina crucible, thereby obtaining a molten alloy. The obtained molten alloy was cast by a strip casting method using the casting device shown in Figure 9, to obtain a cast alloy ribbon (alloy for RTB-based permanent magnets). Casting was performed in an Ar atmosphere.

[0086] The temperature of the molten alloy, the roll surface roughness Rz of the chill roll, and the molten metal head pressure were appropriately selected so as to obtain the alloy for RTB rare permanent magnets shown in Table 2. Specifically, the temperature of the molten alloy (casting temperature) was selected within the range of 1300 to 1600°C, the roll surface roughness Rz of the chill roll was selected within the range of 5 to 50 μm, and the molten metal head pressure was selected within the range of 5 to 25 mm. The material of the chill roll was a copper alloy. The roll peripheral speed of the chill roll and the supply speed of the molten metal to the chill roll (supply speed per unit contact width between the molten metal and the chill roll) were adjusted to the values ​​shown in Table 2 below.

[0087] (Measurement of the area ratio of each tissue) The area ratio of each structure in the RTB permanent magnet alloy was measured using an electron microscope (manufactured by JEOL Ltd.).

[0088] First, samples for evaluation were taken. Specifically, in a process in which one production lot of RTB permanent magnet alloys was supplied by the above-mentioned strip casting method, alloy flakes were sampled from the RTB permanent magnet alloys supplied at regular time intervals. Thirty alloy flakes were randomly taken from the RTB permanent magnet alloys, and each alloy flake was used as an evaluation sample.

[0089] Next, the thickness of the collected evaluation samples was measured. Of the 30 evaluation samples, the 2nd, 3rd, and 4th thickest samples were selected as thick samples, the 14th, 15th, and 16th thickest samples were selected as near average samples, and the 27th, 28th, and 29th thickest samples were selected as thin samples.

[0090] Next, the area ratio of each texture in the cross section was measured for each of the nine selected evaluation samples. Specifically, the magnification of the electron microscope was set at 350 times to set the observation range. The observation range was selected from the observation surface of each evaluation sample in an average state. The length of the observation range in the thickness direction was set to the average thickness of each sample. This is to include both the roll surface and the free surface. The length in the direction perpendicular to the thickness direction was set to 270 μm. The area ratio of each texture was measured for the above nine samples and averaged. The results are shown in Table 2. The column "Texture 3 + 5" in Table 2 represents the total area ratio of texture 3 and texture 5. The column "Texture 1a + 1b + 3 + 5" in Table 2 represents the total area ratio of texture 1a, texture 1b, texture 3, and texture 5.

[0091] (Production of RTB permanent magnets) After hydrogen was absorbed into the RTB permanent magnet alloy at room temperature, hydrogen was removed in a vacuum at 600°C for 1 hour (coarse pulverization) to obtain an alloy powder (coarse pulverized powder). In this example, each step from the hydrogen pulverization to sintering (fine pulverization and molding) was carried out in an Ar atmosphere with an oxygen concentration of less than 50 ppm or in a vacuum.

[0092] Next, zinc stearate and stearic acid amide were added to the alloy powder as grinding aids and mixed using a Nauta mixer. The amount of zinc stearate added was 0.05 parts by mass per 100 parts by mass of the coarsely ground powder. The amount of stearic acid amide added was 0.05 parts by mass per 100 parts by mass of the coarsely ground powder. Then, fine grinding was performed using a jet mill to obtain a finely ground powder with an average particle size of about 3.0 μm.

[0093] The resulting finely pulverized powder was filled into a die placed in an electromagnet, and compacted in a magnetic field by applying a pressure of 120 MPa while applying a magnetic field of 1200 kA / m to the die, to obtain a compact.

[0094] The obtained green body was then sintered by holding it in a vacuum at 1,050°C for 4 hours and then rapidly cooled to obtain a sintered body having the magnet composition shown in Table 1. The obtained sintered body was then subjected to a two-stage aging treatment at 900°C for 1 hour and at 500°C for 1 hour (both in an Ar atmosphere) to obtain an RTB-based permanent magnet (RTB-based sintered magnet).

[0095] [Magnetic properties] The Br, HcJ and Hk / HcJ of each sample were measured using a BH tracer. Br was measured at room temperature for all samples. In Examples 1 to 4 and Comparative Example 1, HcJ and Hk / HcJ were measured at room temperature. In the other Examples and Comparative Examples, HcJ and Hk / HcJ were measured at 150°C. Note that Hk in this example is the value of the magnetic field when the magnetization is Br x 0.9 in the second quadrant of the demagnetization curve.

[0096] [Table 1]

[0097] [Table 2]

[0098] From Examples 1 to 4 and Comparative Example 1, the RTB permanent magnets of Examples 1 to 4 produced using alloys for RTB permanent magnets in which the area ratio of texture 5 was 0.5% or more and 20% or less had higher Br, comparable HcJ, and higher Hk / HcJ than the RTB permanent magnet of Comparative Example 1 produced using an alloy for RTB permanent magnets produced under the same conditions except that the area ratio of texture 5 was outside the above range. In particular, Hk / HcJ at room temperature was higher.

[0099] From Examples 5 to 11, Examples 6 to 11, in which the total area ratio of Structure 1a, Structure 1b, Structure 3 and Structure 5 in the RTB permanent magnet alloy was 4.0% or more and 27.0% or less, had higher HcJ than Example 5, which was produced under the same conditions except that the total area ratio of Structure 1a, Structure 1b, Structure 3 and Structure 5 in the RTB permanent magnet alloy was less than 4.0%.

[0100] From Examples 6 to 11, it was found that the RTB permanent magnets produced under the same conditions except that the total area ratio of Structure 3 and Structure 5 in the RTB permanent magnet alloy was changed from 1.0% to 24.0% tended to have higher HcJ as the total area ratio of Structure 3 and Structure 5 in the RTB permanent magnet alloy was higher.

[0101] In Comparative Example 2, the B content was 0.96 mass%, which was higher than the other Examples. Therefore, even under casting conditions similar to those of the other Examples, the area ratio of the non-columnar crystal structure, especially the area ratio of Structure 5, decreased. As a result, HcJ decreased compared to the Examples. [Explanation of symbols]

[0102] 1...Chill crystal structure 3...Microscopic dotted R-rich phase-containing structure 4…Punctate R-rich phase-containing structure 5...Micro-linear R-rich phase-containing structure 6...Large dot-like R-rich phase-containing structure 7…Normal organization 11…Main phase 13…R-rich phase 21...Cooling roll 23…Tundish 25…Molten alloy 27…Molten metal head pressure

Claims

1. An R-T-B system alloy for permanent magnets containing R, T and B, R being a rare earth element, T being a transition metal element and B being boron, the area ratio of a fine linear R-rich phase-containing structure in a cross section being 0.5% or more and 20.0% or less, the total area ratio of the fine linear R-rich phase-containing structure and the fine dotted R-rich phase-containing structure is 3.6% or more and 23.4% or less; In the fine linear R-rich phase-containing structure, the linear R-rich phases contained in the fine linear R-rich phase-containing structure have a length of 4 to 125 μm and a width of 0.3 to 10 μm, and the intervals between the linear R-rich phases are 1.0 to 1.8 μm, and when the fine linear R-rich phase-containing structure is locally cut into polygonal regions at locations where the lengths, widths and density of the linear R-rich phases differ, the polygonal regions have a major axis of 30 μm or more and 200 μm or less and a minor axis of 5 μm or more and 150 μm or less, The R-T-B system permanent magnet alloy has a fine dotted R-rich phase-containing structure, in which the dotted R-rich phase contained in the fine dotted R-rich phase-containing structure has a size of 0.3 to 1.5 μm in terms of circle equivalent diameter, the number of the dotted R-rich phases per unit area is 0.25 / μm or more, and when the fine dotted R-rich phase-containing structure is locally cut into polygonal regions at locations where the dotted R-rich phase's circle equivalent diameter and density differ, the polygonal regions have a major axis of 10 μm or more and a minor axis of 5 μm or more and 80 μm or less.

2. An R-T-B system alloy for permanent magnets containing R, T and B, R being a rare earth element, T being a transition metal element and B being boron, the area ratio of a fine linear R-rich phase-containing structure in a cross section being 0.5% or more and 20.0% or less, a total area ratio of the chill crystal structure, the fine linear R-rich phase-containing structure, and the fine dotted R-rich phase-containing structure is 4.3% or more and 26.2% or less; In the fine linear R-rich phase-containing structure, the linear R-rich phases contained in the fine linear R-rich phase-containing structure have a length of 4 to 125 μm and a width of 0.3 to 10 μm, and the intervals between the linear R-rich phases are 1.0 to 1.8 μm, and when the fine linear R-rich phase-containing structure is locally cut into polygonal regions at locations where the lengths, widths and density of the linear R-rich phases differ, the polygonal regions have a major axis of 30 μm or more and 200 μm or less and a minor axis of 5 μm or more and 150 μm or less, The R-T-B system permanent magnet alloy has a fine dotted R-rich phase-containing structure, in which the dotted R-rich phase contained in the fine dotted R-rich phase-containing structure has a size of 0.3 to 1.5 μm in terms of circle equivalent diameter, the number of the dotted R-rich phases per unit area is 0.25 / μm or more, and when the fine dotted R-rich phase-containing structure is locally cut into polygonal regions at locations where the dotted R-rich phase's circle equivalent diameter and density differ, the polygonal regions have a major axis of 10 μm or more and a minor axis of 5 μm or more and 80 μm or less.

3. An R-T-B system alloy for permanent magnets as described in claim 2, wherein the total area ratio of the fine linear R-rich phase containing structure and the fine dotted R-rich phase containing structure is 3.6% or more and 23.4% or less.

4. 4. An R-T-B system alloy for permanent magnets according to claim 1, wherein the R content is 29.0 mass % or more and 33.5 mass % or less, and the B content is 0.70 mass % or more and less than 0.96 mass %.

5. A method for producing an RTB system permanent magnet, comprising the step of pulverizing the RTB system permanent magnet alloy according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Rare earth magnetic alloy sheet, its manufacturing method, sintered rare earth magnetic alloy powder, sintered rare earth magnet, metal powder for bonded magnet, and bonded magnet

    JP2003188006A

  • Method for producing rare-earth containing alloy flake, alloy flake for rare-earth magnet, alloy powder for rare-earth sintered magnet, rare-earth sintered magnet, alloy powder for bonded magnet and bonded magnet, and evaluation method for metallic structure

    JP2004181531A

  • Alloy slug for r-t-b-based sintered magnet, manufacturing method therefor and magnet

    JP2005320628A

  • Alloy for r-t-b-based rare earth sintered magnet, method for manufacturing the same, alloy material for the same, r-t-b-based rare earth sintered magnet, method for manufacturing the same, and motor

    JP2013216965A

  • Fine particle rare earth alloy flakes, manufacturing method thereof, and rotary cooling roll device

    JP2020503686A